Service Quality of Consulting Business-To-Business From Engineers of Oil and Gas Company in: A Case Study of PT. LAPI ITB - Lokasthiri Az, Jene; Fachira, Ira (Journal of Business and Management, 2015)
Abstract . The development of globalization has induced the need for universities that capable to develop independent and democratic society to compete internationally. Through the Government Regulation Nr. 155/ 2000, ITB was legalized to be State Owned Legal Entity (BHMN). Being so, ITB has greater autonomy to regulate itself complemented with greater responsibility to improve its competitiveness in the global world with commercial business unit, which is PT. LAPI ITB. PT. LAPI ITB engaged in consultancy and training. This research explores about concept of service quality in B2B context. The calculation based on dimensions used in this research has been adjusted from B2C to B2B, which are Responsiveness, Credibility, Consultative Selling, Reliability, Competence and Price as the dimension (Westbrook and Peterson, 1998). This new form of SERVQUAL in B2B context expected to be able to reflect customer gap score of expected and real performance of PT. LAPI ITB. Which with the 110 of correspondents based on 10% of finished projects in term of 2014, resulted that the gap of performance service and expected service is negative, which means that PT. LAPI ITB did not perform their service especially in Responsiveness, Credibility, Consultative Selling, Reliability, Competence and Price. Analyzing this dimension of SERVQUAL in PT. LAPI ITB has resulting that an improvement of service is quite necessary for their company. However, based on the result of customer’s expectation in consulting (B2B context) fairly high enough. This might happen because customer fully entrust the job to PT. LAPI ITB, and the result of projects and assignments is important for their company’s work process. So its normal for the company to expect the highest possibility of performance.Keywords: Marketing Research; Service Quality; Business-to-Business Context.